2012
DOI: 10.1093/brain/aws143
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of autophagy reduces neurodegeneration in a mouse model of human tauopathy

Abstract: The accumulation of insoluble proteins is a pathological hallmark of several neurodegenerative disorders. Tauopathies are caused by the dysfunction and aggregation of tau protein and an impairment of cellular protein degradation pathways may contribute to their pathogenesis. Thus, a deficiency in autophagy can cause neurodegeneration, while activation of autophagy is protective against some proteinopathies. Little is known about the role of autophagy in animal models of human tauopathy. In the present report, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
228
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(250 citation statements)
references
References 56 publications
14
228
1
1
Order By: Relevance
“…It will now be important to identify the molecular mechanisms that account for the low and unbalanced bone remodeling caused by suppression of autophagy in osteocytes. In addition, recent studies in other organs, such as the brain and liver, have demonstrated that stimulation of autophagy can prevent or reverse age-associated damage (52,53). Thus, it will also be important to complement our loss-of-function studies with gain-of-function studies to determine whether maintenance or stimulation of autophagy in osteocytes is sufficient to prevent any aspects of skeletal aging.…”
Section: Discussionmentioning
confidence: 99%
“…It will now be important to identify the molecular mechanisms that account for the low and unbalanced bone remodeling caused by suppression of autophagy in osteocytes. In addition, recent studies in other organs, such as the brain and liver, have demonstrated that stimulation of autophagy can prevent or reverse age-associated damage (52,53). Thus, it will also be important to complement our loss-of-function studies with gain-of-function studies to determine whether maintenance or stimulation of autophagy in osteocytes is sufficient to prevent any aspects of skeletal aging.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Of note, the chemical-induced enhancement of autophagy has been reported to decrease aggregates in the CNS and retard the progression of neurological symptoms in several animal and cell culture models of neurodegenerative diseases, including TSE. [14][15][16][17][18][19] The autophagy-lysosomal system is regulated by several mechanisms, one example of which is mechanistic target of rapamycin (MTOR) signaling. 20 FK506, also named tacrolimus, is well known as an immunosuppressive drug that is mainly used post-transplantation to decrease the activity of the recipient's immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Trehalose is considered to enhance autophagic activity (21). It has been shown to promote the cellular clearance of pathogenic proteins like mutant huntingtin, ␣-synuclein (21,22), and phosphorylated tau (22)(23)(24) that are associated with Huntington, Parkinson, and Alzheimer diseases, respectively. However, the role of trehalose in the cellular metabolism of the Alzheimer disease-associated APP remains to be investigated.…”
mentioning
confidence: 99%